2012
DOI: 10.1002/jctb.3787
|View full text |Cite
|
Sign up to set email alerts
|

Biological conversion of CO2 to CH4 using hydrogenotrophic methanogen in a fixed bed reactor

Abstract: BACKGROUND: Biological conversion of CO 2 to useful carbonic compounds such as methane is a potentially attractive technology for reducing its concentration in the atmosphere. One of the advantages of this technology over chemical conversion is that it requires much lower energy for reduction of CO 2 . In this article, biological conversion of CO 2 to CH 4 using hydrogenotrophic methanogens was examined in a fixed bed reactor inoculated with anaerobic mixed culture from the anaerobic digestor of a sewage treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(48 citation statements)
references
References 11 publications
(18 reference statements)
3
43
1
1
Order By: Relevance
“…Firstly, the addition of H 2 to anaerobic digesters of organic matter in order to remove CO 2 from biogas while increasing the production of biomethane Wang et al, 2013) and, secondly, the supply of H 2 and a CO 2 (or biogas) to an exclusively methanogenic bioreactor rich in hydrogenotrophic archaeas (Burkhardt and Busch, 2013;Ju et al, 2008;Kim et al, 2013;Lee et al, 2012;Peillex et al, 1990). Both lines of research found that the barrier to the successful development of the technology on an industrial scale is the gas-liquid mass transfer of H 2 , due to its low solubility (dimensionless Henry's constant, H H 2 = 50 and 55 g=L G =g=L H 2 O at 35 and 55°C, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the addition of H 2 to anaerobic digesters of organic matter in order to remove CO 2 from biogas while increasing the production of biomethane Wang et al, 2013) and, secondly, the supply of H 2 and a CO 2 (or biogas) to an exclusively methanogenic bioreactor rich in hydrogenotrophic archaeas (Burkhardt and Busch, 2013;Ju et al, 2008;Kim et al, 2013;Lee et al, 2012;Peillex et al, 1990). Both lines of research found that the barrier to the successful development of the technology on an industrial scale is the gas-liquid mass transfer of H 2 , due to its low solubility (dimensionless Henry's constant, H H 2 = 50 and 55 g=L G =g=L H 2 O at 35 and 55°C, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…This is, CH 4 is transferred alongside with CO 2 and H 2 from the gas into the liquid phase, reducing the gas to liquid mass transfer of H 2 /CO 2 [22,30], which was found to reduce the volumetric CH 4 productivity tremendously [30]. In this respect, bioreactors other than stirred tank reactors could be considered [9], [41,42]. Furthermore, high volumetric CH 4 productivities are usually demanded for industrial processes.…”
Section: Discussionmentioning
confidence: 98%
“…They are inhabitants of the anaerobic reactor, which has been regarded as an attractive process for the reduction of various types of compounds. Our previous study showed that CO 2 fed to the fixed bed reactor inoculated with anaerobic mixed culture from the anaerobic digestor of sewage treatment plant was reduced with H 2 without organic carbon source [6]. Methane formation commenced on the first day of operation of the fixed bed reactor.…”
Section: Introductionmentioning
confidence: 99%